The Role of Diet in Influencing the Diversity of Gut Microbiome Related to Lupus Disease Activities: A Systematic Review - Putri, Prisly Z.; Hamijoyo, Laniyati; Sahiratmadja, Edhyana (International Journal of Microbiology, 2022)
Gut microbiome dysbiosis can affect the host immune system. The balance and activity of the gut microbiome, which are influenced by daily diet, might be associated with disease activity in systemic lupus erythematosus (SLE). Therefore, we conducted a systematic review based on the PRISMA guideline to explore the role and types of diet that affects the gut microbiome related to changes in SLE disease activity. All original and full-text English articles in the last ten years were included using predefined keywords according to PEO (population, exposure, and outcome) design in PubMed. The study subjects were carefully analyzed, including lupus-susceptible mice and humans with SLE on various diets. Children and pregnant women populations were excluded. Of 134 studies found, only seven full-text articles had met the inclusion criteria of which only one study conducted in human. This human study showed that dietary polyphenol as dihydrochalcones and flavanones affected the gut microbiome and ameliorated lupus disease activity. On the contrary, dietary flavones increased Blautia (family: Lachnospiraceae), and that often found in active lupus diseases. Furthermore, six studies in lupus-prone mice models showed that resistant starch (RS), retinoic acid (RA) or all-trans retinoic acid (tRA), and acidic water (AW) had influenced the gut microbiome, leading to an improved lupus development. Conversely, the 2018 commercial rodent diet, vitamin A-retinoic acid (VARA), neutral water (NW), and high tryptophan diet had impacted various microbiomes, resulting in increased lupus activity. Interestingly, several diets have the effect of either increasing or decreasing lupus disease activity depending on the microbiome they affect, such as AW associated with Turicibacter spp., which is frequently found in active lupus disease, and tRA in Bacteroidetes associated with renal pathology. To conclude, diet can influence the gut microbiome, which is related to the disease activity process of SLE.